Teoria e prática na formação de professores: contribuições freireanas - um olhar sobre a experiência do município de Santo André, SP (1990-2010) - Joanete, Marisa Peres Ballones (2011)
The present study aims to investigate the theory practice, in the public policies context of the permanent development of the teachers of the elementary school, in the city of Santo André. The research aims to know and analyze the perception of teachers of the elementary school of the municipality in respect to the relation theory practice in their trajectory of graduation, during the 1990 to 2010 period, and to propose indications to the public policies. For this, we seek to answer the following question: how the teachers which use successful practices perceive the theory practice relation into the context of the permanent development of the teachers? To reach the proposed objective, the research of the qualitative character with a descriptive and interpretative approach, into a dialectic perspective, seek to investigate subjacent intentionality and ideology to the public policies of the development of teachers. This subject is going to be realized analyzing official documents and field research, investigating with the individuals of the educative practice, teachers with successful practices, how is the conscientiousness of the non-sociability between theory and practice, clarifying their reflections and theories. The itinerary of the research will have as a leading axle the theory practice categories, permanent development of teachers and dialog, based in the freireanos context, in a denunciation and advise , which contextualize the perceived problem and points indications as possible ways to overcame this subject